Comparing the Primary and Secondary Stability of Compressive One-Piece Implants with Conometric Cap vs. Compressive-M Implants - Shaswar, Omer Aziz; Al-Zahawi, Abdulsalam R. (Sulaimani Journal for Pure and Applied Sciences, 2021)
Background: This research was conducted to assess and compare the stability of compressive one-piece implants with conometric caps and compressive-M implants (screw type) at the time of implant insertion, three months, and six months after insertion. Experimental: A total of 15 patients (8 females and 7 males) with a mean age of 54 ± 17.5 years participated in this study. A total of 82 implants from two implant designs (ROOTT Compressive implants with conometric caps and ROOTT Compressive-M implants with screw-type prosthesis) were placed in the lower premolar-molar areas using standard surgical protocols. The implant stability test (IST) readings were clinically measured by the Anycheck implant stability meter in both buccal and lingual directions immediately after insertion of the implant (T0), three months (T1), and six months (T2) after insertion. Results: The results displayed that the highest mean value was 63.17 using IST for Compressive implants with conometric caps on the buccal direction at T2, while the lowest mean value was 52.47 for Compressive-M implants with a screw-type prosthesis at T1. The comparison of mean values of IST showed statistically significant (P<0.05) differences between Compressive implants and Compressive-M implants at T1 and T2 but non-significant differences at T0 in both buccal and lingual directions. The mean IST values for the 39 compressive implants in lingual direction were 61.83 at T0, 59.77 at T1, and 61.57 at T2, while the mean IST values for the 35 Compressive-M implants in the same order were 59.4, 51.2, and 52.13 at T0, T1, and T2, respectively. Conclusion: We found that the stability of Compressive conometric implants is higher than that of Compressive-M implants in both T1 and T2.
Keywords: One-piece implant; Compressive-M implant; conometric cap; Anycheck implant stability meter; implant stability test; screw type